KURATOWSKI I-CONVERGENT DOUBLE SEQUENCES OF A CLOSED SETS ON INTUITIONISTIC FUZZY NORMED SPACE - Hira Fatima, Jayantika Pal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Motivated by the notion of Kuratowski convergence of sequences of closed set [20]. In this paper, we extend the concept of Kuratowski convergence to Kuratowski ideal convergence with respect to intuitionistic fuzzy normed space for a double sequence of closed sets and rectify some properties for this new de ned double sequence spaces.